Aspek-Aspek Program Keluarga Berencana yang Berkaitan Dengan Hukum Pidana - Sriwati Sakkirang (Al-'Adl, 2008)
The family planning program is an enterprise that regulates the number of births in such a way that for both mother and baby and for the father and his family or the community concerned will cause harm as a direct result of the birth. This national program, undertaken by the community with help, support and full protection by the government. Efforts to prevent pregnancy is one of the main activities undertaken in running the family planning program.        Family planning is a deliberate human effort to organize or plan a pregnancy in a family unlawfully and morally for family welfare.